The Elements of Materia Medica and Therapeutics. Volume 2Part 1 - Pereira, Jonathan (Place of publication not identified : publisher not identified, 1855)
After training as an apothecary and surgeon, Jonathan Pereira (1804-53) taught materia medica for many years. His lectures at the medical school in London's Aldersgate Street were highly successful and formed the basis for the first edition of his major encyclopaedic work on medicinal substances. A pioneering text in the field of pharmacology, Pereira's work, which he subsequently updated in further editions, provided pharmacists and medical professionals with a more rigorous scientific understanding of the drugs and remedies they prescribed. After Pereira's death, medical jurist Alfred Swaine Taylor (1806-80) and physician George Owen Rees (1813-89) prepared this revised and expanded fourth edition, interspersed with instructive woodcuts. Volume 2 is divided into two parts. Part 1 (1855) continues with articles on special pharmacology, moving on from inorganic compounds to discuss the medicinal properties of organic compounds.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).